Women Entrepreneurs with New Age Media - Sen, Dr. Gautam (International Journal of Scientific Research and Management (IJSRM), 2017)
Almost all the people in our country collects and gets information about government, entertainment, sports, market, employment and so on through media. Media in include print media, electronic media and new age media. Media plays a very important role in the development of a society. Women are considered as an important part of the society. Now a days women are playing a great role in the development of society by converting themselves as entrepreneurs. Women entrepreneurs create new jobs not only for themselves but also for others and provide variety of solutions of the problems faced by the society and by the management, organization and other business houses. However, they still represent a minority of all entrepreneurs. Women entrepreneurs often face gender-based barriers to starting and growing their businesses, like discriminatory property, matrimonial and inheritance laws and/or cultural practices; lack of access to formal finance mechanisms; limited mobility and access to information and networks, etc. In this paper an attempt has been made to identify the role of new age media in the enhancement of women of entrepreneurship. Results indicate that women entrepreneurs are not using the new age media as a good medium to promote their products and business.